A CHECKLIST OF THE FAMILY LAUXANIIDAE (DIPTERA, LAUXANIOIDEA) IN VIETNAM, MAINLY WITH THE SUBFAMILY LAUXANIINAE - Hyun Suk Lee (Tạp chí Khoa học Đại học Đà Lạt)
I reviewed the lauxaniid literature as many as possible and listed any lauxaniid species with Vietnamese records. In this paper, I provided a taxonomic checklist of 41 nominal species under two subfamilies Homoneurinae and Lauxaniinae. In total, the number of lauxaniid species in Vietnam became 101 species belong to 21 genera. The Homoneurinae consists of 6 genera and 63 species. The Lauxaniinae includes 15 genera and 38 species. These two checklists will be the fundamental base for comprehensive taxonomic research of lauxaniid fauna in Vietnam.